Comprehensive Proteome and Lysine Acetylome Analysis Reveals the Widespread Involvement of Acetylation in Cold Resistance of Pepper (Capsicum annuum L.) - Liu, Zhoubin; Song, Jingshuang; Miao, Wu; Yang, Bozhi; Zhang, Zhuqing; Chen, Wenchao; Tan, Fangjun; Suo, Huan; Dai, Xiongze; Zou, Xuexiao; Ou, Lijun (Frontiers in Plant Science, 2021)
Pepper is a typical warmth-loving vegetable that lacks a cold acclimation mechanism and is sensitive to cold stress. Lysine acetylation plays an important role in diverse cellular processes, but limited knowledge is available regarding acetylation modifications in the resistance of pepper plants to cold stress. In this study, the proteome and acetylome of two pepper varieties with different levels of cold resistance were investigated by subjecting them to cold treatments of varying durations followed by recovery periods. In total, 6213 proteins and 4574 lysine acetylation sites were identified, and this resulted in the discovery of 3008 differentially expressed proteins and 768 differentially expressed acetylated proteins. A total of 1988 proteins were identified in both the proteome and acetylome, and the functional differences in these co-identified proteins were elucidated through GO enrichment. KEGG analysis showed that 397 identified acetylated proteins were involved in 93 different metabolic pathways. The dynamic changes in the acetylated proteins in photosynthesis and the “carbon fixation in photosynthetic organisms” pathway in pepper under low-temperature stress were further analyzed. It was found that acetylation of the PsbO and PsbR proteins in photosystem II and the PsaN protein in photosystem I could regulate the response of pepper leaves to cold stress. The acetylation levels of key carbon assimilation enzymes such as ribulose bisphosphate carboxylase, fructose 1,6 bisphosphatase, sedoheptulose 1,7 bisphosphatase, glyceraldehyde 3 phosphate dehydrogenase, phosphoribulokinase, and triosephosphate isomerase decreased, leading to decreases in carbon assimilation capacity and photosynthetic efficiency, reducing the cold tolerance of pepper leaves. This study is the first to identify the acetylome in pepper, and it greatly expands the catalog of lysine acetylation substrates and sites in Solanaceae crops, providing new insights for post-translational modification studies.